2003
DOI: 10.1017/s0305000902005500
|View full text |Cite
|
Sign up to set email alerts
|

Genre and evaluation in narrative development

Abstract: In this study I examine Venezuelan children's developing abilities to use evaluative language in fictional and personal narratives. The questions addressed are: (1) How does the use of evaluative language vary in fictional and personal narratives? (2) Is there a relationship between the use of evaluative language in these two narrative genres and children's age and socio-economic status (SES)? The sample consists of 444 narratives produced by 113 Venezuelan school-age children participating in 4 narrative task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
0
62

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(150 citation statements)
references
References 29 publications
4
84
0
62
Order By: Relevance
“…The increasing available data suggest that Spanish-speaking children tend to produce narratives that differ from other cultural/linguistic groups (Bocaz, 1989;Gutiérrez-Clellen & Heinrichs-Ramos, 1993;Gutiérrez-Clellen & Quinn, 1995;Sebastián & Slobin, 1994;Shiro, 2003). In a comparative study of narratives produced by low-income African American and Latino children (from Central America and the Caribbean), Rodino, Gimbert, Perez, and McCabe (1991) found that Latino children did not generally narrate using sequences of events but instead favored description and evaluation.…”
Section: Sociocultural Contextmentioning
confidence: 99%
“…The increasing available data suggest that Spanish-speaking children tend to produce narratives that differ from other cultural/linguistic groups (Bocaz, 1989;Gutiérrez-Clellen & Heinrichs-Ramos, 1993;Gutiérrez-Clellen & Quinn, 1995;Sebastián & Slobin, 1994;Shiro, 2003). In a comparative study of narratives produced by low-income African American and Latino children (from Central America and the Caribbean), Rodino, Gimbert, Perez, and McCabe (1991) found that Latino children did not generally narrate using sequences of events but instead favored description and evaluation.…”
Section: Sociocultural Contextmentioning
confidence: 99%
“…The increased pause time in the storybook narrative seems to be related to cognitive and linguistic gaps, thus evidencing the gradual process of formation of concepts, lexical items and assimilation of syntactic rules for structuring the narrative speech (6,7,8,9,10,11,18). This also might be a strategy for the speaker to get more time to repair the mistakes in the narrative production or even to follow actions such as page changes (18).…”
Section: Discussionmentioning
confidence: 96%
“…With regard to spontaneous narrative, the findings were not significant. In fictitious narrative, for example, it was observed the presence of secondary elements and insertion of non-true contents, although sporadic adult intervention may occur to help make the speech coherent and fluent (7,9,11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations